The Role of ER Stress-Induced Apoptosis in Neurodegeneration - C. Stefani, Ioanna; Wright, Daniel; M. Polizzi, Karen; Kontoravdi, Cleo (Current Alzheimer Research, 2012)
Post-mortem analyses of human brain tissue samples from patients suffering from neurodegenerative disorders have demonstrated dysfunction of the endoplasmic reticulum (ER). A common characteristic of the aforementioned disorders is the intracellular accumulation and aggregation of proteins due to genetic mutations or exogenous factors, leading to the activation of a stress mechanism known as the unfolded protein response (UPR). This mechanism aims to restore cellular homeostasis, however, if prolonged, can trigger pro-apoptotic signals, which are thought to contribute to neuronal cell death. The authors present evidence to support the role of ER stress-induced apoptosis in Alzheimer’s, Parkinson’s and Huntington’s diseases, and further examine the interplay between ER dyshomeostasis and mitochondrial dysfunction, and the function of reactive oxygen species (ROS) and calcium ions (Ca2+) in the intricate relationship between the two organelles. Possible treatments for neurodegenerative diseases that are based on combating ER stress are finally presented.
Keywords: neurodegeneration